Activities of navy chaplains in organising libraries on ships of the Russian Imperial Navy at the turn of the 19th and 20th centuries - Sozont Singh; Ekaterina Konopleva (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi)
The activity of the navy chaplains outside the framework of worship is still a little-studied aspect of the service of the Orthodox clergy in the navy. This article attempts, based on the analysis of various written sources, to reconstruct the activities of representatives of the naval clergy in organizing libraries on the ships of the Russian Imperial Navy in the late 19th - early 20th centuries. This is one of the least studied areas of ministry of navy chaplains. The authors, relying on personal sources, office materials and periodicals, analyze the existing practice in the fleet of creating and completing ship libraries, their types and features of functioning, and also determine the role of navy chaplains in these processes. It is important to note that many sources are introduced into scientific circulation for the first time. The authors came to the conclusion that, despite the frequent lack of initiative on the part of the officers or even with a certain opposition, the navy chaplains were directly related to the organization of both church and sailor's libraries. Some clerics acted quite effectively in this field, but they could not significantly change the general situation that had developed with librarianship on the ships of the Russian Imperial Navy.